Multigap Resistive Plate Chambers for Time of Flight Applications - Yi Wang; Yancheng Yu (Applied Sciences, 2020)
With the advantages of high-performance, easy to build and relatively low cost, the multigap resistive plate chamber has been arousing broad interests over the last few decades. It has become a new standard technology for the time of flight system in high energy physics experiments. In this article, we will give a description of the structure and the operating principles of the MRPC detector and focus on reviewing the applications on the time of flight system in several famous experiments. The performances, including time resolution and particle identification, are discussed in detail. Some recent advances and points of view for the future development of the next generation MRPC are also outlined.